KELAYAKAN USAHATANI VARIETAS UNGGUL KACANG TANAH DI KABUPATEN HALMAHERA UTARA - Bayu Suwitono (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2018)
ABSTRACT Feasibility Of Peanut Farming Of The New Superior Varieties Of Bean In North Halmahera Regency,Peanut farming in North Maluku is mainly grown in dry land with low level of productivity due to some factors. One of them is due to the low adoption of high-yielding varieties of seeds. Indonesian Agency for Agricultural Research and Development (IAARD) has developed superior varieties for peanut commodities. The objective of the research was to identify adaptive high yielding varieties of peanuts with high production potential and to analyze the feasibility of peanut farming in North Maluku. Research was conducted in Tiowor Village, North Halmahera District, from February to November 2014. Four high yielding varieties of peanuts namely Hipoma, Talam, Bima, and Tuban and one local variety were cultivated by applying the integrated crop management (ICM) technology. Results showed that the high yielding varieties tested had high level of adaptation.  Bima peanuts was the most adaptive variety producing 3.79 ton/ha. Peanut variety Bima and peanut local variety were the most feasible varieties to be developed. The R/C ratios of peanut farming using these two varieties were 4.35 and 4.57, respectively.Keywords: Peanut, High yielding variety, farming, feasibility, adaptive. ABSTRAK Usahatani kacang tanah di Maluku Utara dominan di lahan kering dengan tingkat produktivitas yang masih rendah. Hal ini disebabkan oleh banyak faktor di antaranya rendahnya penggunaan benih varietas unggul. Di sisi lain, Balitbangtan mempunyai banyak varietas unggul untuk komoditas kacang tanah. Tujuan penelitian adalah untuk mendapatkan Varietas Unggul kacang tanah yang adaptif dengan produksi tinggi dan menganalisa kelayakan usahatani  kacang tanah. Penelitian dilakukan di Desa Tiowor Kabupaten Halmahera Utara pada bulan Februari sampai November 2014. Empat varietas unggul kacang tanah yang terdiri atas Hipoma, Talam, Bima dan Tuban serta satu varietas lokal ditanam dengan pendekatan Pengelolaan Tanaman Terpadu (PTT). Hasil penelitian menunjukan bahwa varietas unggul yang diuji memiliki tingkat adaptasi yang tinggi di lokasi kajian.  Kacang tanah Bima merupakan varietas yang paling adaptif dengan produksi 3,79 ton/ha. Secara finansial  Kacang tanah varietas Bima dan  lokal paling layak dikembangkan dengan R/C ratio sebesar 4,35 dan 4,57. Kata kunci: Kacang tanah, Varietas unggul, Usahatani, kelayakan, Adaptif